Ecotourism Development Strategy In Improving Rural Creative Economy In Bone Bolango District - Suaib Napir; Muthen S Nuna (Universitas Gorontalo, 2022)
In order to support the development of the rural creative economy in Bone Bolango Regency, ecotourism development techniques need to be thoroughly examined. The purpose of this study is to identify the ecotourism development plan for enhancing the rural creative economy in Bone Bolango Regency. In order to obtain the necessary data for this study, interviews, observations, and literature reviews were used. The data obtained will be more thoroughly examined using this strategy. The study's findings include the following: First, the development of natural ecotourism, marine ecotourism, historical ecotourism, and the construction of tourism awareness groups constitute the ecotourism development strategy. The plan, meanwhile, has not been the most effective in boosting the Bone Bolango district's rural creative economy.Therefore, the bone bolango regency administration needs a strategic policy to support the growth of ecotourism in connection with enhancing the creative economy. Second, the impact of ecotourism development on the economy of rural communities in the bone bolango district has not been fully realized, given that only three of the 16 ecotourism potentials are natural, and that only the Lombongo tourism potential contributes 0.9 percent of the levy, 2.5% of the levy from Olele Submarine Park, and 0.2% of the levy from Botutonuo Beach.